Enhancement of resilience of teenage fathers using narrative therapy - Lara, Francesca A. (College of Education, University of the Philippines Diliman, 2019)
The study investigated on teenage fathers and the change in their resiliency level after exposure to narrative therapy sessions. It also recognized the factors that facilitated and hindered their resilience. A total of seven teenage fathers participated in the study. The factors identified that facilitate teenage fathers; resilience are receiving financial and childcare assistance, assistance from the school and community, guidance, diversion, and basic knowledge of child-rearing. The identified factors that hinder resilience are conflict experienced by teenage fathers, unemployment, severe criticism, personal desires, insufficient awareness of childcare, and having concurrent roles. Participants reported that Narrative Therapy enhanced their ability to reflect on concerns, increased their opportunity to share them, and boosted their confidence in solving problems and creating plans for the future.